Analisis Masalah Pengumpulan dan Pendistribusian Dana Zakat di BAZNAS Provinsi Bangka Belitung dengan metode dekomposisi masalah (Metode Analytic Network dekomposisi masalah (Metode Analytic Network - Irvani, Ahmad; Wulpiah, Wulpiah (EJESH: Journal of Islamic Economics and Social, 2024)
Zakat plays a crucial role in enhancing social welfare and reducing poverty. This research aims to analyze the core challenges in collecting and distributing zakat funds in BAZNAS Bangka Belitung Province using the Analytic Network Process (ANP) method. Key findings indicate that organizational aspects, human resources limitations, operational budget constraints, and weak monitoring mechanisms significantly hinder zakat management. The study recommends strategic solutions such as creating a mustahik database, enhancing human resource capabilities, adopting transparent monitoring systems, and diversifying funding sources. Implementing these strategies can potentially improve zakat management efficiency and effectiveness in reducing poverty in Bangka Belitung Province.